New evidence for age differences, within-person declines and plasticity in the aging white matter: new MRI techniques and analytical approaches - Mendez Colmenares, Andrea, author; Thomas, Michael L., advisor; Burzynska, Agnieszka Z., advisor; Davalos, Deana, committee member; Fisher, Gwen, committee member; Hamilton, Karyn, committee member (Colorado State University. Libraries, 2023)
White matter deterioration leads to cognitive impairments in healthy aging, Alzheimer's disease, and related dementias. Therefore, it is critical to identify interventions that can slow the white matter deterioration. Animal studies have suggested that the white matter plays an active role in brain plasticity and learning. However, evidence for experience-induced plasticity in adult human white matter remains scarce and inconsistent, especially in older age. To accurately predict the effects of interventions on the white matter, we first need to understand the direction and magnitude of naturally occurring within-person changes across adulthood. To date, white matter in aging, Alzheimer's disease, and related dementias have been studied almost solely using diffusion MRI, which provides limited information about the white matter microstructure. Because there is little evidence of white matter plasticity in adult humans, white matter has rarely been considered as a target for interventions against dementia. This dissertation comprises three scientific articles investigating the mechanisms of white matter decline and plasticity. The first article presents a study using a novel technique (T1w/T2w imaging) to examine the effects of aerobic exercise on aging white matter in a randomized controlled trial. The second article is a meta-analysis and systematic review of within-person changes in white matter. The third article shows the first application of a multimodal fusion analysis to study healthy aging white matter. Through these innovative approaches, this dissertation provides new insights into the mechanisms of white matter decline and plasticity, paving the way for the development of effective interventions to promote healthy brain aging.
Keywords: MRI; white matter; aging; within-person decline; plasticity